Dislocation plasticity in FeCoCrMnNi high-entropy alloy: quantitative insights from in situ transmission electron microscopy deformation. Issue 6 (2nd June 2020) - Lee, Subin; Duarte, María Jazmin; Feuerbacher, Michael; Soler, Rafael; Kirchlechner, Christoph; Liebscher, Christian H.; Oh, Sang Ho; Dehm, Gerhard
ABSTRACT: The mechanical properties of high-entropy alloys (HEAs) are still not deeply understood. Detailed knowledge of the strengthening mechanism, especially, the atomistic origin of solid solution hardening and its interplay with dislocation plasticity is needed. Here, we report on the dislocation glide behavior of a FeCoCrNiMn face-centered cubic (FCC) single crystal studied by in situ deformation in a transmission electron microscope (TEM). The threshold shear stress for dislocation glide in a thin foil is measured from dislocation curvature as exceeding 400 MPa. Interestingly, dislocations are prevented from straightening upon unloading due to high frictional stresses. GRAPHICAL ABSTRACT: IMPACT STATEMENT: The fiction stress for dislocation glide in a FeCoCrMnNi HEA is assessed by direct measurement of dislocation line curvature during in situ TEM deformation, which is higher compared to other FCC metals, explaining the outstanding yield and flow stress of the HEA.